Perspective of the Development of Ethno-Economics and Ethno-Management towards Sustainable Development in Rural and Urban Areas - Wiliandri, Ruly; Ardianwiliandri, Raditya (Ekonomi Bisnis, 2024)
This paper explores the influence of socio-demographic and socio-economic factors on traditional economic systems, focusing on rural and urban areas in Indonesia. It highlights how cultural traditions like familism shape economic practices, particularly in agricultural communities. The study employs qualitative methods, including interviews with key informants, to examine economic behavior in Senduro village (rural) and Cemorokandang subdistrict (urban). Findings reveal that extended families and lower education levels in rural areas contribute to the persistence of traditional economies, while urban areas with higher education and more stable incomes lean towards modern economic practices. Future research could explore additional factors, such as psychosocial or environmental influences, to provide a more comprehensive understanding of this dynamic relationship.